2020
DOI: 10.1063/5.0023405
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced hierarchical ripples in MoS2 layers investigated by atomic force microscopy

Abstract: Strain engineering plays a vital role in controlling the physical properties of two-dimensional (2D) materials. However, the nanomechanical behavior of atomically thin 2D crystals under strain has not been completely understood. Here, strain-induced hierarchical ripple nanostructures in triangular MoS2 flakes were investigated by advanced atomic force microscopy and optical spectral measurements. The hierarchical nanoripples exhibited a threefold radial pattern, and their mechanical, electronic, and optical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…In addition to the compressive strain, the tensile strain can also induce a ripple structure within the thin 2D films. 14,19,22 The thermal tensile strain-induced hierarchical ripples in MoS 2 monolayer flakes have been observed in our previous work. 14 At here, the in-plane stretch/tension at the rear area of the sliding tip will also induce the ripple reformed along the direction of the tip sliding (Figure 5h).…”
Section: ■ Results and Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition to the compressive strain, the tensile strain can also induce a ripple structure within the thin 2D films. 14,19,22 The thermal tensile strain-induced hierarchical ripples in MoS 2 monolayer flakes have been observed in our previous work. 14 At here, the in-plane stretch/tension at the rear area of the sliding tip will also induce the ripple reformed along the direction of the tip sliding (Figure 5h).…”
Section: ■ Results and Discussionsupporting
confidence: 67%
“…14,19,22 The thermal tensile strain-induced hierarchical ripples in MoS 2 monolayer flakes have been observed in our previous work. 14 At here, the in-plane stretch/tension at the rear area of the sliding tip will also induce the ripple reformed along the direction of the tip sliding (Figure 5h). By the simultaneous "pushing" and "stretching" mechanism, the new rippling domain was formed via the reorientation of rippling lines.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Following the discovery of graphene prepared by the micromechanical exfoliation technique, 1 much research intension has been paid on the two-dimensional (2D) [2][3][4][5][6][7] material due to its superior characteristic properties, including excellent physical, 8,9 mechanical, 10,11 chemical, 12,13 electronic and optoelectronic properties. [14][15][16][17] One of the intriguing advantages of the 2D layered material is that their isotropic properties can be converted to be anisotropic, which results from the breaking symmetry owing to their intrinsic puckering behaviors.…”
mentioning
confidence: 99%
“…Nanomechanical deformation has been extensively investigated by the atomic force microscopy (AFM) indentation experiments on suspended films. [21][22][23] Based on AFM platform, [24][25][26][27] friction force microscopy (FFM) and transverse shear microscopy (TSM), as the derivative mode of contact AFM, [28][29][30][31][32] now have been widely used to study the elastic deformation, 19,31 crystal structure, 28 surficial ripples of 2D materials 8,34,35 and so on. Such studies have revealed an important phenomenon in which nanomechanical contact behavior could be dependent on the number of layers and substrates.…”
mentioning
confidence: 99%